The effect of core strength training on 14-year-old soccer players' agility, anaerobic power, and speed - Mossa, M. E. (American Journal of Sports Science, 2022)
The football players must be physically fit, technically adept, strategically well-equipped, and mentally prepared to withstand the pressures of the game. Among those essential components, physical fitness is the basis. So, coaches implemented aerobics, strength, and power training for large muscle groups. However, the core muscles, which assist maintain balance, transform stored energy into explosive strength, and enable robust kicking and leaping activities, have received little attention. The goal of this study is to investigate how core strength training improves soccer players' agility, muscular power, and speed. We utilized a true patterned experimental design and randomly selected 13 players as the control group (CG) and 13 players as the experimental group (EG). A pre-test was conducted by both groups' players (agility, anaerobic power and speed tests). In addition to the standard soccer training program, the EG was utilized for core strength training twice a week for three months, for 30 to 35 minutes each day. The coach only implemented regular soccer training on the CG. We repeated the measurements three months later on the same parameter. And agility grew considerably (MD in TT of EG was 0.738) at P = 0.000, the difference between MD in TT of CG 0.3769 at P = 0.005 and MD in TT of CG 0.3769 at P = 0.005 is reasonably significant. IAT's pre- and post-test mean of EG and CG do not differ significantly, other than their great improvement. However, both groups' IAT results improved significantly (MD and P value of EG in was significantly decreased by a MD of 0.381, P 0.00. and 0.3685, P 0.017 in case of CG). EG`s anaerobic power (before and after MD and P value in VJT) was .06 at P = 0.000, which was larger than CG's MD of .0254 at P = .038. Furthermore, the pre and post MD and P values in the SLJT of EG and CG are .1161 at P = 0.003 and .0308 at P = .052, respectively. Furthermore, in the 10m dash test of EG and CG, the MD and P value of the speed test were .1392 at P .020 and .1206 at P .020, respectively. In the 40-meter dash speed test, EG and CG had pre and post MD of .2015 at P .008 and .1293 at P .010, respectively. Generally, three months of core strength training increased the speed, power, and agility of 14-year-old EG much more than CG.